The Influence of Brand Experience on Willingness to Pay a Premium Price with Brand Loyalty and Brand Love as mediating variables on Viu application users, especially K-drama lovers in Padang City: Pengaruh Brand Experience terhadap Willingness To Pay A Premium Price dengan Brand Loyalty dan Brand Love sebagai variabel mediasi pada pengguna aplikasi Viu khususnya penikmat K-drama Di Kota Padang - Mona Ratu Chania; Yunita Engriani (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the effect of brand experience on willingness to pay a premium price with brand loyalty and brand love as mediating variables on Viu application users, especially K-Drama lovers in Padang City. The research method used is quantitative with the Structural Equation Modeling (SEM) approach using Smart PLS 4 software. Data were collected from 313 respondents who are Viu users in Padang City. The results of the study indicate that brand experience has a significant effect on brand loyalty and brand love. In addition, brand loyalty and brand love act as mediation in increasing willingness to pay a premium price. The conclusion of this study confirms that a positive experience in using the Viu application contributes to increasing user loyalty and love for the brand, which ultimately encourages them to be willing to pay a premium price